(untitled) (Research, Society and Development, 2020)
The adoption of information and communication technologies (TIC) in the most diverse sectors of the economy, reflects the current competitive scenario, in which processes and practices can be optimized, providing significant changes in business models. In this sense, this article describes the development of Chatbot for the classification of soybeans and calculations of discounts on the grain load, thus making it possible to compare the Chabot classification data with the data from the grain storage units. Thus, considering the significant increase in monthly conversations with chatbots through messaging platforms and the conversational relationship between organizations and users, as well as the lack of a device that would meet the demand of the producer to carry out in real time the classification of soybeans, which this project was developed. Initially, interviews and visits were carried out in grain storage units, as a technique for surveying requirements. The project was developed in JavaScript language, NoSql database and Dialogflow console for Chatbot development. In the end, it was possible to verify that the system created for soybean farmers performs classification and discount calculations, avoiding losses in each harvest, in a comfortable, agile manner and following Normative Instruction 11/2007 of the Ministry of Agriculture, Livestock and Supply (MAPA), which sets the official soy classification standard.